In the anytime: Flexible time structures, student experience and temporal equity in higher education. (November 2019) - Bunn, Matthew; Bennett, Anna; Burke, Penny J
Time is often taken-for-granted as abstract and constant, even though the lives we lead are always changing within the context of time and because of time. In this paper, we explore the hidden challenges of hegemonic neoliberal framings of 'flexibility' which urge students to presume that study-time is asynchronous and can be engaged with anytime, eroding recognition that it is contextual and much more structured than expected. Timing is dynamic and shifts in relation to broader economic, spatial and cultural changes, all of which shape the 'temporal dis/positions' we discuss. A study that included 27 interviews with Australian university students is drawn on to illuminate these points. We argue that through the neo-liberalised projection of the university, important contextual dynamics and associated demands are increasingly disguised. This impacts on learning and teaching time and individualises responsibility for time management onto students, many of whom consequently experience guilt and self-blame.